Sleeving nanocelluloses by admicellar polymerization - Trovatti, Eliane [UNESP]; de Medeiros Ferreira, Adriane; Carvalho, Antonio José Felix; Ribeiro, Sidney José Lima [UNESP]; Gandini, Alessandro (Elsevier, 2013)
This investigation reports the first application of admicellar polymerization to cellulose nanofibers in the form of bacterial cellulose, microfibrillated cellulose, and cellulose nanowhiskers using styrene and ethyl acrylate. The success of this physical sleeving was assessed by SEM, FTIR, and contact angle measurements, providing an original and simple approach to the modification of cellulose nanofibers in their pristine aqueous environment. © 2013 The Authors. Published by Elsevier Inc.
Keywords: Admicellar polymerization; Nanocellulose